Cruces de ganado de doble propósito en la zona montañosa baja colombiana, 1. Peso corporal hasta los 18 meses. - Hernández B., Gustavo; Moreno O., Fernando; Carvajal R., Guillermo (Instituto Colombiano Agropecuario, 2019)
There are few studies that report the growth rate up to 18 months of Bar tauru.c-Bo.v indicus crosses under the dual purpose system, which is important for the total appraisement of the system. The purpose of the work was to compare the growth rate of two pure breeds, five F1, one F2, and two three way crosses in a mountainous zone (800 to 1200 meters) of north central Colombia. The animals were grazing with wather and mineral mixture at libjiwn. The calves remained with their dams for 8 hours after partial milking of them. Weaning was at nine months of age. Data was analysed by least squares methods and the means were compared by Tukey test. The breed effect was highly significant (P 0.01) for the five independent variable analysed. The Bos taurus-Bos in(/icu.r F1 (Red Holstein x Zebu, Brown Swiss x Zebu, Normande x Zebu and Blanco Orelinegro x Zebu) had a weaning and 18 months weights of 151.0 and 249.9 kg and surpassed the Zebu by 5.3 and 9.1%, respectively. The Brown Swiss x Zebu excelled the Brown Swiss x Blanco orejinegro by 16.0 and 34.5% for weaning and 1 8months weights, respectively. The corresponding advantages of F Red Holstein x Zebu over the F2 Black Holstein x Zebu were of 15.9 and 13.2%. The crosses Brown Swiss (Zebu x Blanco Orejinegro) and Zebu (Black Holstein x Blanco Orejinegro), althoug having crossbred dams, their weaning weight were 3.3% below Zebu weight, nevertheless for 18 months weight it showed a small recovery (2% over Zebu). The study results make emphasis on the importance of hybrid vigor especially in the first cross.